The locomotor activity of soccer players based on playing positions during the 2010 World Cup - Soroka, A. (The Journal of Sports Medicine and Physical Fitness, 2018)
BACKGROUND: The aim of this study was to define the locomotor activity of footballer players during the 2010 World Cup and to assess what differences existed among different playing positions. METHODS: Research was conducted using research material collected from the Castrol Performance Index, a kinematic game analysis system that records player movements during a game by use of semi-automatic cameras. A total of 599 players who participated in the championships were analyzed. The results were evaluated using one-way analysis of variance (ANOVA) and a post-hoc test that calculated the Honestly Significant Difference (HSD) in order to determine which mean values significantly differed among the player positions. RESULTS: It was found that midfielders covered on average the largest distance during a match (10,777.6 m, P<0.001) as well as performing the most locomotor activity at high and sprint intensities (2936.8 m and 108.4 m, respectively). Additionally, midfielders also spent the largest amount of time at performing at a high intensity (10.6%). Strikers also featured high levels of the above parameters; the total length of distance covered with high intensities was found to be on average 2586.7 m, the distance covered at sprint intensity was 105 m. CONCLUSIONS: The footballers, playing at the championship level feature excellent locomotor preparation. This fact is undoubtedly supported by the aerobic training of high intensity. Such training allows footballers to extend the distance they cover during the match, increase the intensity of locomotor activities and sprint speed distance.